2016
DOI: 10.1186/s12913-016-1803-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a video-based education and process change intervention to improve advance cardiopulmonary resuscitation decision-making

Abstract: BackgroundAdvance cardiopulmonary resuscitation (CPR) decision-making and escalation of care discussions are variable in routine clinical practice. We aimed to explore physician barriers to advance CPR decision-making in an inpatient hospital setting and develop a pragmatic intervention to support clinicians to undertake and document routine advance care planning discussions.MethodsTwo focus groups, which involved eight consultants and ten junior doctors, were conducted following a review of the current litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 31 publications
0
34
0
1
Order By: Relevance
“…The workshop utilised locally developed videos during a draft phase 16 and (i) focused on clinical issues related to CPR decision-making, (ii) promoted the use of an ethical decision-making framework 12 and (iii) explored clinical communication using the video scenarios. The workshop utilised locally developed videos during a draft phase 16 and (i) focused on clinical issues related to CPR decision-making, (ii) promoted the use of an ethical decision-making framework 12 and (iii) explored clinical communication using the video scenarios.…”
Section: Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The workshop utilised locally developed videos during a draft phase 16 and (i) focused on clinical issues related to CPR decision-making, (ii) promoted the use of an ethical decision-making framework 12 and (iii) explored clinical communication using the video scenarios. The workshop utilised locally developed videos during a draft phase 16 and (i) focused on clinical issues related to CPR decision-making, (ii) promoted the use of an ethical decision-making framework 12 and (iii) explored clinical communication using the video scenarios.…”
Section: Interventionsmentioning
confidence: 99%
“…The second part of the two-pronged strategy was a structured 2-h workshop for ward medical staff. The workshop utilised locally developed videos during a draft phase 16 and (i) focused on clinical issues related to CPR decision-making, (ii) promoted the use of an ethical decision-making framework 12 and (iii) explored clinical communication using the video scenarios. The content focused on patients with progressive, deteriorating illness.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second 6-month period (March-August 2017) was considered the intervention arm and investigated the implication of an inclusive four-treatment phase GOC form (Supporting Information Files S2, S3) adapted from previous local and interstate concepts. 2 The GOC arm of the study requested that treating consultants complete a GOC form for every patient admitted to the designated wards within 48 h of hospitalisation. While strongly encouraged through various educational means listed in Appendix S1, completion was not mandated.…”
Section: Designmentioning
confidence: 99%
“…19,24,25 Physician-related barriers include a lack of communication skills, 22 discomfort in discussing death and dying, 24 and fear of causing distress. 26 System-level barriers include time pressures, 21,26 lack of quality professional mentorship, 24,26 few guidelines on discussing EOL issues, 24 and lack of training around communicating about EOL. 21,24,26 These factors could explain why a recent Australian study found that only one-quarter of patients referred to the intensive care unit (ICU) had a documented GOC discussion.…”
mentioning
confidence: 99%